The Urgency of Habituating Students’ Religious Behavior in Islamic Elementary Schools - Nanda Fitriana Putri; Imam Muslih (Journal Of Islamic Education And Pesantren, 2023)
Religious education in madrasahs plays a strategic role in shaping students’ religious character. Its effectiveness largely depends on the strategies used to internalize values and consistently cultivate religious behaviors. Religious education is not merely oriented toward the transfer of knowledge but emphasizes character formation and the habituation of moral conduct in accordance with Islamic teachings. Moral deviations in children are often associated with weak value formation during their developmental stages. Therefore, madrasahs need to foster a religious culture through systematic habituation practices to develop discipline, responsibility, and adherence to religious norms, particularly in responding to the challenges of globalization. This study aims to describe the urgency of habituating religious behavior among students at MI Salafiyah Syafi’iyah Jatirejo. The research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The findings indicate that the madrasah consciously implements religious habituation activities as an effort to bring students closer to Allah SWT, cultivate discipline, and instill consistent religious behavior in daily life. Such habituation serves as a fundamental foundation for developing students’ noble character and their adaptability to contemporary societal changes.